(untitled) (Journal on studies and research of academic knowledge, 2014)
Maintaining blood glucose values in considered safe levels in newboms (RN) has always been a concern of pediatricians to prevent brain damage. up to now, there is no consensus on this value. This paper aims to establish the incidence of hypoglycemia in healthy newborns: in the maternity of Encarnación Regional Hospital (HRE). It was found that the incidence of hypoglycemia was 6% in the population studied. Of these, 78 % were born by Caesarean section, 22 % were pre term, and 11% of post- term. Regarding on weight, 11% were small for gestational age. Regarding the type of feeding 149 children were exclusively breastfed and 5% were positive for hypoglycemia, 2 were mixed-fed and 50 % had hypoglycemia and 2 received artificial feeding, not presenting hypoglycemia neither. It can be conclude that there was not found a significant relationship between hypoglycemia and each variable studied, but when associated two or more variables.